A study on energy conservation behavioural intention among secondary school students at Sekolah Menengah Kebangsaan Ibrahim (SMK Ibrahim) / Siti Nur Aini Yaacob and Nur Ayuni Ahmad - Yaacob, Siti Nur Aini; Ahmad, Nur Ayuni (2018)
This paper study on Energy Conservation Behavioural Intention among Secondary school students at Sekolah Menengah Kebangsaan Ibrahim (SMK Ibrahim). This study examines the influence of attitude, subjective norms and perceived behavioural control towards energy conservation behavioural intention among Secondary school students using Theory of Planned Behaviour (TPB). Data collected about 242 from the total population 650 of students based on the table proposed by Uma Sekaran and Bougie (2003). The methodologies used descriptive analysis, correlation and multiple regressions for test analysis. The result from the analysis shows that there is significant relationship of dependent variable which is energy conservation behavioural intention and independent variables namely attitude, subjective norms and perceived behavioural control. The result of the analysis also shows the most influential factor influence energy conservation behavioural intention is attitude.